A Peculiar Tracheoesophageal Fistula Caused by a Plastic Foreign Body - Chao Chen; Dingyuan Dai; Yu Guo; Chen Sun; Qi Li (Case Reports in Otolaryngology)
The occurrence of tracheoesophageal fistula (TEF) in children is commonly attributed to the presence of foreign bodies. This paper presents a unique case admitted to the Children’s Hospital of Nanjing Medical University on August 9, 2022, where a plastic fragment resembling a doll’s eye was identified as the precipitating factor. The report investigates the unusual trajectory of this case—examining the pathway through which the foreign body became lodged in the trachea, followed by the subsequent development of TEF—and provides valuable insights into its pathogenesis and clinical significance.